THE MECHANISM AND THE DYNAMICS OF LANDSLIDE PROCESSES IN THE CENTRAL PART OF KYIV ON THE RIGHT BANC OF DNEPR - HOLUB, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Factors, which play important role in appearance and activization of landslide processes on the right banc slope of Dnepr in the central part, have been considered. Mechanism of landslide processes has been defined. Characteristic of modern conditions of the area and activity of landslides have been given.